Mesoporous silica nanoparticles: Their potential as drug delivery carriers and nanoscavengers in Alzheimer's and Parkinson's diseases - Mohamed S. Attia; Ahmed Yahya; Nada Abdel Monaem; Shereen A. Sabry (Elsevier, 2023)
Worldwide, populations face significant burdens from neurodegenerative disorders (NDDs), especially Alzheimer's and Parkinson's diseases. Although there are many proposed etiologies for neurodegenerative disorders, including genetic and environmental factors, the exact pathogenesis for these disorders is not fully understood. Most patients with NDDs are given lifelong treatment to improve their quality of life. There are myriad treatments for NDDs; however, these agents are limited by their side effects and difficulty in passing the blood-brain barrier (BBB). Furthermore, the central nervous system (CNS) active pharmaceuticals could offer symptomatic relief for the patient's condition without providing a complete cure or prevention by targeting the disease's cause. Recently, Mesoporous silica nanoparticles (MSNs) have gained interest in treating NDDs since their physicochemical properties and inherent ability to pass BBB make them possible drug carriers for several drugs for NDDs treatment. This paper provides insight into the pathogenesis and treatment of NDDs, along with the recent advances in applying MSNs as fibril scavengers. Moreover, the application of MSNs-based formulations in enhancing or sustaining drug release rate, and brain targeting via their responsive release properties, besides the neurotoxicity of MSNs, have been reviewed.